1981
DOI: 10.1103/physrevlett.46.838
|View full text |Cite
|
Sign up to set email alerts
|

Abruptness of Semiconductor-Metal Interfaces

Abstract: A predictive relation between reacted interface width and heat of interface reaction is presented for III-V-compound-semiconductor-metal interfaces. Soft-x-ray photoemission measurements reveal that the thickness of chemically reacted species and the extent and stoichiometry of atomic interdiffusion are determined by the strength and nature of metal-semiconductor bonding. Chemical bond strength directly influences the macroscopic electronic properties as shown by transport measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…As the anneal temperature increases to 400°C, a large growth in the Ga oxide peak, at þ1 eV, is seen, and a decrease in the Ga-Ni intensity. This assignment is consistent with interdiffusion between the In 0.53 Ga 0.47 As and Ni layer as has been previously reported for the interaction between Ni and Ga containing semiconductors [34,35]. The subsequent oxidation of the up-diffused Ga, prior to SiN deposition, results in the formation of a surface oxidized overlayer which acts to suppress the Ga-Ni signal.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As the anneal temperature increases to 400°C, a large growth in the Ga oxide peak, at þ1 eV, is seen, and a decrease in the Ga-Ni intensity. This assignment is consistent with interdiffusion between the In 0.53 Ga 0.47 As and Ni layer as has been previously reported for the interaction between Ni and Ga containing semiconductors [34,35]. The subsequent oxidation of the up-diffused Ga, prior to SiN deposition, results in the formation of a surface oxidized overlayer which acts to suppress the Ga-Ni signal.…”
Section: Resultssupporting
confidence: 91%
“…In addition to the oxide growth, the lower BE peak at −0.5 eV is attributed to a Ga-Ni bonding interaction at the surface based on the respective electronegativities of both Ga (1.81) and Ni (1.91) [33]. The reaction between Ga and Ni has been studied previously on GaAs and the observed strong interaction between Ni and Ga [12] was attributed to the large enthalpy of formation for NiGa [34]. As the anneal temperature increases to 400°C, a large growth in the Ga oxide peak, at þ1 eV, is seen, and a decrease in the Ga-Ni intensity.…”
Section: Resultsmentioning
confidence: 99%
“…These experimental results indicate that deposition of metal stabilizes (or pins) the Fermi level at the interface. There were several attempts to understand this phenomenon in terms of screening [9], formation of new phases [10,11 ], or formation of localized states at the M-S interface. N possible localized states and the mechanisms of their formation have been hotly debated issues.…”
Section: Defecf Induced Stabilization Of Fermi Energymentioning
confidence: 99%
“…2 In the past several years, with the development of microanalytical techniques, it has been found that the interaction at a metal-semiconductor interface is generally not weak and reactions frequently occur, resulting in atomistic changes of the layer, e.g., compound formation, defect generation, and interatomic mixing. 3 "" 6 These phenomena modify the stoichiometry, atomic environment, and microstructure of the interface, which can change the basic nature of the interface states.…”
mentioning
confidence: 99%